SYARIAH OBLIGATION: PROSPECTS AND ITS CHALLENGES IN INDONESIA - Sudirman, Sudirman; Bakri, Bakri (Al-Ulum, 2015)
This writing is designed to investigate prospects and challenges facing Syariah Obligation (sukuk) in Indonesia. In this study, we found Syariah obligation (sukuk) development have good prospect. There are factors supporting Syariah obligation (sukuk) in Indonesia, some of which are significant population, government support, and domestic economic stability over percent per year, flow of fresh fund by Middle East, and making complete regulatory framework, as well as the rise of global Syariah market. Notwithstanding sukuk potential, some challenges are exist, for examples, drawback of regulation, uncertainty of taxation, most of Syariah financial products are âdebt-basedâ or âdebt-likelyâ, less investor understanding of Syariah obligation instrument, and not quite conducive investment climateÂ  and complicated bureaucracy. Â -----Tulisan ini bertujuan untuk mengkaji prospek dan tantangan obligasi syariah (sukuk) di Indonesia. Pada penelitian ini, ditemukan bahwa prospek pengembangan obligasi syariah (sukuk) di Indonesia cukup baik. Terdapat beberapa faktor yang mendukung keberadaan obligasi syariah (sukuk) di Indonesia, antara lain: jumlah penduduk yang banyak, dukungan dari pemerintah, Stabilitas perekonomian dalam negeri, di atas persen pertahun, mengalirnya dana segar dari timur tengah, dan regulatory farmework yang cukup memadai, serta bangkitnya pasar global syariah. Meskipun potensi sukuk cukup baik, tetapi tetap saja memiliki sejumlah tantangan, antara lain: adanya kelemahan dari aspek regulasi, ketidakpastian dari segi perpajakan, kebanyakan produk keuangan syariah bersifatâ debt-basedâatau âdebt-likely, kurangnya pemahaman oleh investor terhadap instrumen obligasi syariah, dan iklim investasi yang kurang kodusif serta birokrasi yang berbeli-belit.